Antioxidant Activity of Spirulina platensis and Sea Cucumber Stichopus hermanii in Streptozotocin-Induced Diabetic Rats - Hema Aprilia Setyo Windari,; Kustiariyah Tarman,; Mega Safithri ,; Iriani Setyaningsih, (Tropical Life Sciences Research, 2019)
Uncontrolled blood glucose level of diabetic people can lead to the production of excessive Reactive Oxygen Species (ROS) as the trigger of lipid peroxidation. Antioxidant can defend the human body from overreacting to lipid peroxidation. The study aimed to determine the antioxidant activity of Spirulina platensis and sea cucumber Stichopus hermanii based on the number of blood serum and liver malondialdehyde (MDA) levels as well as superoxide dismutase (SOD) and catalase (CAT) enzymes’ activity of red blood cells in streptozotocin-induced diabetic rats. A group of Sprague Dawley rats (n=3) were the normal group (aquadest 2 mL/day, p.o.) and group of DM, Sp (S. platensis 81 mg/kg body weight; p.o.), Tr (S. hermanii 284 mg/kg body weight; p.o.), (Combination S. platensis 81 mg/kg + S. hermanii 284 mg/kg body weight; p.o.) prior to a single dose of streptozotocin (STZ, 50 mg/kg body weight; i.p.). The results showed that S. platensis, sea cucumber (S. hermanii), and the mixture could suppress rats’ body weight by 2–7%. The MDA concentration of liver organ of rats prior to STZ administration increased. However, the STZ administration did not significantly increase MDA concentration of blood serum and decreased activity SOD and CAT of red blood cells in the normal group for 14 days. This study concluded that Spirulina platensis demonstrated antioxidant activity indicated by the reduction of MDA level in the liver of diabetic rats induced by STZ (50 mg/kg body weight; i.p.).